2020
DOI: 10.1093/ee/nvaa023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Constant and Fluctuating Temperature on the Development, Reproduction, Survival, and Sex Ratio of Phenacoccus solenopsis (Hemiptera: Pseudococcidae)

Abstract: Effects of temperature on the development, survival, reproduction, longevity and sex ratio of the cotton mealybug, Phenacoccus solenopsis Tinsley, was assessed at five constant temperatures ranging from 20 to 35°C and five fluctuating temperatures ranging from 15 to 40°C under laboratory conditions. Results showed that nymphal development duration, preoviposition period, oviposition period, fecundity, and adult longevity were reduced significantly with increasing temperature until 30°C, but developmental durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…At present, compared with more reports focusing on the impact of high temperature on the distribution [ 3 , 13 , 23 , 32 ], survival [ 15 ], development [ 16 , 17 ], and reproduction [ 17 , 24 ] of P. solenopsis and its parasitoid, there are relatively few reports on morphological characteristics. Phenotype is the result of the interaction of genetic factors and environmental factors (biological and abiotic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, compared with more reports focusing on the impact of high temperature on the distribution [ 3 , 13 , 23 , 32 ], survival [ 15 ], development [ 16 , 17 ], and reproduction [ 17 , 24 ] of P. solenopsis and its parasitoid, there are relatively few reports on morphological characteristics. Phenotype is the result of the interaction of genetic factors and environmental factors (biological and abiotic).…”
Section: Discussionmentioning
confidence: 99%
“…In some countries, this mealybug causes severe economic damage to cotton and to a wide range of vegetables, horticultural plants and other field crops [ 14 ]. At present, many studies have reported the effects of temperature on the survival rate [ 15 ], development [ 16 ], and reproduction [ 17 ] of P. solenopsis . These studies showed that P. solenopsis had strong temperature adaptability [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though it cannot do so indefinitely (mateless females only produce males), sex ratio responses can improve populations' chances of persistence. This mechanism may not, however, be restricted to haplodiploids: some diploid species may adjust sex ratio in response to environmental factors or sperm limitation (Lehtonen and Schwanz 2018, Waqas et al 2020). Diploid pollinators (fungus gnats) of Lepanthes orchids may ejaculate on flowers; sex ratios of these gnats become more male‐biased at cold temperatures (Nigro et al 2007, Pandey and Tripathi 2008, Farsani et al 2013) which prevail when Lepanthes orchids flower.…”
Section: Discussionmentioning
confidence: 99%